Novel Quantitative Trait Loci for Grain Cadmium Content Identified in Hard White Spring Wheat - Qiao, Ling; Wheeler, Justin; Wang, Rui; Isham, Kyle; Klassen, Natalie; Zhao, Weidong; Su, Meng; Zhang, Junli; Zheng, Jun; Chen, Jianli (Frontiers in Plant Science, 2021)
Cadmium (Cd) is a heavy metal that can cause a range of adverse human health effects, including cancer. Wheat comprises approximately 20% of the human diet worldwide, thus reducing Cd concentrations in wheat grain will have significant impacts on Cd intake in food products. Tests for measuring grain Cd are costly and content is affected significantly by soil pH. To facilitate breeding for low Cd content, the present study sought to identify quantitative trait loci (QTL) and associated molecular markers that can be used in molecular breeding. One spring wheat population of 181 doubled haploid lines, which was derived from a cross between two hard white spring wheat cultivars ‘UI Platinum’ and ‘LCS Star’, was assessed for grain Cd content in multiple field trials in Southeast Idaho, USA. Three major QTL, QCd.uia2-5B, QCd.uia2-7B, and QCd.uia2-7D, were identified on chromosomes 5B, 7B, and 7D, respectively. All genes in the three QTL regions were identified from the NCBI database. Three of these genes related to Cd uptake and transport were used in the candidate gene analysis. Sequences of gene TraesCS5B02G388000 (TaHMA3) in the QCd.uia2-5B region and genes TraesCS7B02G320900 (TaHMA2) and TraesCS7B02G322900 (TaMSRMK3) in the QCd.uia2-7B region were compared between UI Platinum and LCS Star. Gene TaHMA2 on 7B is proposed for the first time as a candidate gene for grain Cd content in wheat. A KASP marker associated with this gene was developed and will be further validated in near-isogenic lines and via a gene editing system in future studies.